Blood Flow Restricted Exercise and Vascular Function. (22nd October 2012) - Horiuchi, Masahiro; Okita, Koichi
Abstract : It is established that regular aerobic training improves vascular function, for example, endothelium-dependent vasodilatation and arterial stiffness or compliance and thereby constitutes a preventative measure against cardiovascular disease. In contrast, high-intensity resistance training impairs vascular function, while the influence of moderate-intensity resistance training on vascular function is still controversial. However, aerobic training is insufficient to inhibit loss in muscular strength with advancing age; thus, resistance training is recommended to prevent sarcopenia. Recently, several lines of study have provided compelling data showing that exercise and training with blood flow restriction (BFR) leads to muscle hypertrophy and strength increase. As such, BFR training might be a novel means of overcoming the contradiction between aerobic and high-intensity resistance training. Although it is not enough evidence to obtain consensus about impact of BFR training on vascular function, available evidences suggested that BFR training did not change coagulation factors and arterial compliance though with inconsistence results in endothelial function. This paper is a review of the literature on the impact of BFR exercise and training on vascular function, such as endothelial function, arterial compliance, or other potential factors in comparison with those of aerobic and resistance training.